The unit group of the group algebra F_q(Z_9 timesZ_3) - Sharma, R. K.; Kumar, Yogesh; Mishra, D. C. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 512.5 Let p be a prime, F_q be a finite field with q=p^n elements, and Z_9 timesZ_3 be the semidirect product of the groups Z_9 and Z_3. The unit group U(F_q(Z_9 timesZ_3) of the group algebra F_q(Z_9 timesZ_3) is completely characterized.